2022
DOI: 10.4014/jmb.2112.12050
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Activity of Extremely Effective Recombinant L-Asparaginase fromBurkholderia pseudomallei

Abstract: L-asparaginase (E.C. 3.5.1.1) purified from bacterial cells is widely used in the food industry, as well as in the treatment of childhood acute lymphoblastic leukemia. In the present study, the Burkholderia pseudomallei L-asparaginase gene was cloned into the pGEX-2T DNA plasmid, expressed in E. coli BL21 (DE3) pLysS, and purified to homogeneity using Glutathione Sepharose chromatography with 7.26 purification fold and 16.01% recovery. The purified enzyme exhibited a molecular weight of ~33.6 kDa with SDS-PAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…According to our knowledge, there are only a few reports on antiproliferative or proapoptotic effects induced by novel source L-asparaginases in AML (e.g., THP-1) and promyelocytic (e.g., HL-60) cell lines. It has been reported, for example, that L-asparaginase from Burkholderia pseudomallei (GenBank: ABA50799.1, class 1, type II), which has no detectable L-glutaminase activity, affects the viability of THP-1 cells [51]. As THP-1 cells are more sensitive to the depletion of L-Gln than L-Asn, these data conflict with our observations.…”
Section: Discussioncontrasting
confidence: 99%
“…According to our knowledge, there are only a few reports on antiproliferative or proapoptotic effects induced by novel source L-asparaginases in AML (e.g., THP-1) and promyelocytic (e.g., HL-60) cell lines. It has been reported, for example, that L-asparaginase from Burkholderia pseudomallei (GenBank: ABA50799.1, class 1, type II), which has no detectable L-glutaminase activity, affects the viability of THP-1 cells [51]. As THP-1 cells are more sensitive to the depletion of L-Gln than L-Asn, these data conflict with our observations.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, EDTA acted as inhibitors of LA from Streptomyces brollosae NEAE-115 activity reducing its activity by 37.55 (El-Naggar et al, 2018). it was revealed that EDTA decreased the activity of B. pseudomallei LA by 60.7 and 41.2%, respectively, at concentrations of 1 mM and 5 mM (Darwesh et al, 2022).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, Abbas et al (2015) reported the highest LA activity after 10 min of incubation at 37 º C, and observed the gradual decrease in enzyme activity by increasing the time to incubation beyond 10 min. Darwesh et al, (2022) reported optimum pH of 8 for enzyme action from Burkholderia pseudomallei. LA from Bacillus licheniformis, T. viride HK01 and Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…FLAG, poly-His, poly-Arg, Stre-taq, c-Myc, and S-taq are the most commonly used affinity peptide tags because their small size interferes with the protein of interest. Small ubiquitin-related modifier (SUMO) [109], maltose-binding protein (MBP) [110], N-utilization protein A (NusA), thioredoxin (Trx) [111], glutathione-S-transferase (GST) [112], disulfide isomerase I (PDI), Fasciola hepatica antigen (Fh8) and Superfolder green fluorescent protein (sfGFP) are examples of protein tags that improve protein solubility. Examples of insolubility-enhancing tags are N-terminal autoprotease (Npro), β-barrel outer membrane protein (PagP) and two smaller sulfur carrier proteins (ThiS) and (MoaD).…”
Section: Fusion Tagsmentioning
confidence: 99%